The perceptions of small business owners and consumers on the implementation of a tax lottery system to improve tax compliance behaviour in South Africa - Schoeman, Anculien (University of Pretoria, 2023)
Mini Dissertation (MCom (Taxation))--University of Pretoria, 2022.